2011
DOI: 10.1063/1.3672190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chain stiffness and salt concentration on responses of polyelectrolyte brushes under external electric field

Abstract: We report a molecular dynamics study on non-equilibrium dynamics of polyelectrolyte brushes under external electric fields. In this work, the effects of chain stiffness and salt concentration on static and dynamic responses of the brushes are addressed in detail. Our simulations indicate that varying these parameters induce rich electro-responsive behavior of the brushes. The increase of salt concentration results in the enhancement of an opposite electric field formed by non-equilibrium distribution of cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The brushes adopt various conformational behavior depending on different oppositely charged components and their concentrations. Except for equilibrium brush conformations, molecular simulation works on the polyelectrolyte brushes in external fields, such as electric field [ 23 , 24 , 25 ], have been performed. The electric field can influence the fluid transport in channels coated with polyelectrolyte brushes through changing the conformations of the brushes.…”
Section: Introductionmentioning
confidence: 99%
“…The brushes adopt various conformational behavior depending on different oppositely charged components and their concentrations. Except for equilibrium brush conformations, molecular simulation works on the polyelectrolyte brushes in external fields, such as electric field [ 23 , 24 , 25 ], have been performed. The electric field can influence the fluid transport in channels coated with polyelectrolyte brushes through changing the conformations of the brushes.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have simulated the modulation of electroosmotic flow in polymer-coated channels using molecular dynamics methods [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], providing insights into the role of polymer coatings in controlling the EOF. Additionally, responsive behaviors of charged polymer brushes to the electric field normal to surfaces were also investigated through computer simulations [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ouyang et al25 used molecular dynamics simulations to analyze the gating mechanisms in a polyelectrolyte‐grafted nanochannel under external electric field. Further, our group studied the effects of salt concentration and chain stiffness on response behavior of the brushes under added electric fields 26. These works revealed that polyelectrolyte brushes as the gating components show a strong static and dynamic response to the change of applied electric field.…”
Section: Introductionmentioning
confidence: 99%